A Parasitoid Muscidifurax raptor Girault & Sanders (Insecta: Hymenoptera: Pteromalidae) - Nicholas S.G. Tucker; Philip E. Kaufman (EDIS, 2017)
Includes: Introduction - Synonymy - Distribution - Life Cycle and Description - Hosts - Economic Importance - Selected References